Strategic learning and metacognition - Chávez Herrera, Nathaly Johana (2017)
The development of didactics for the student of this 21st century requires the use of appropriate strategies, where learning is more perceived as the result of the link between the emotional and cognitive aspect and social interactions, focused on establishing a close relationship and communication. The present article offers information about teaching strategies and teaching-learning methods.